Acral Melanoma Incidence and Survival Trends in 1990-2020: A Nationwide, Population-based Study - Teo Helkkula; Gustav Christensen; Rasmus Mikiver; Åsa Ingvar; Karolin Isaksson; Kari Nielsen (Medical Journals Sweden, 2024)
Acral melanoma is a clinical subtype of melanoma with high mortality, on which research is limited in scope. This study aimed to assess incidence trends and melanoma-specific survival rates for acral melanoma in the Swedish population from 1990 to 2020.This cross-sectional study included patients with an acral melanoma diagnosis from 1990 to 2020 from the nationwide, population-based Swedish Melanoma Registry. Analyses on acral melanoma melanoma-specific survival rates were adjusted for age, sex, histopathological subtype, and tumour thickness. Clinicopathological features and melanoma-specific survival rates were compared between diagnostic periods: 1990-1999, 2000-2009, and 2010-2020, respectively. Changes in standardized incidence rates in 1996-2020 were evaluated separately for males and females. In total, 1,000 acral melanomas in 999 patients were included in the study. No significant yearly change in standardized incidence rates for either males or females was observed, even though the absolute number of cases increased. Factors such as male sex, age ≥ 70 years, and Breslow thickness > 1.0 were independently linked to lower melanoma-specific survival. The 5-year melanoma-specific survival across the studied period ranged from 75.8% to 77.9% for females, and from 62.4% to 71.7% for males.